Mental health in a context of urban poverty: a qualitative approach - Carolina Martínez S (Revista Facultad Nacional de Salud Pública, 2009)
Objective: With the premise that there is a strong relationship between mental health problems and the characteristics of the world in which people live, this article analyzes the findings of a qualitative inquiry about the situation of a small group of low-income urban families in Mexico at the end of the 20th century. It proposes also a reflection about the contributions of this kind of approach to achieve a better understanding of the complex constellations that give rise to mental health disturbances in each context. Methodology:The interpretation offered in this paper is oriented by a postkleinian psychoanalytic model developed for the study of the influence of the family and community contexts on the person’s psychic structure. The data analyzed was collected several years ago by means of direct observation and in-depth personal interviews to each member of twenty low-income urban families living in the south of Mexico City. Results:The analysis oriented by this model showed different types of family emotional dynamics and its influence on the psychic structure and function of their members. It was found a low coverage of public health services for this group of population, and specially a lack of preventive and curative mental health services.